Human spaceflight: to infertility and beyond - Cardona Maya, Walter D.; du Plessis, Stefan S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Garrett-Bakelman FE et al, demonstrated a spectrum of molecular and physiological changes attributed to spaceflight in their recently published “NASA Twins Study”.1 During his 340 days in space onboard the International Space Station (ISS), one of a pair of monozygotic twins was not only challenged by noise, isolation, hypoxia, and alterations in the circadian rhythm, but more importantly the exposure to ionizing radiation (IR) and microgravity. Terrestrials are subjected constantly to surface gravity and most if not all physiological processes have adapted accordingly. It is therefore easy to envisage that weightlessness can have consequences for space travellers.2